1999
DOI: 10.1042/bj3420721
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of the cDNA species for mammalian dimeric dihydrodiol dehydrogenases

Abstract: Cynomolgus and Japanese monkey kidneys, dog and pig livers and rabbit lens contain dimeric dihydrodiol dehydrogenase (EC 1.3.1.20) associated with high carbonyl reductase activity. Here we have isolated cDNA species for the dimeric enzymes by reverse transcriptase-PCR from human intestine in addition to the above five animal tissues. The amino acid sequences deduced from the monkey, pig and dog cDNA species perfectly matched the partial sequences of peptides digested from the respective enzymes of these animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Determination of whether the putative bacterial or archaeal sequences of clusters IA and IB represent functional oxidoreductases or (xylose) dehydrogenases must await their biochemical characterization following expression of the genes that encode them. Eukaryotic xylose dehydrogenases-dimeric DDs, (cluster II), which probably represent a novel family of dehydrogenases (1,2), and archaeal glucose dehydrogenases (cluster III), which belong to the medium-chain dehydrogenase-reductase superfamily (26), form distinct phylogenetic clusters separate from the xylose dehydrogenase from H. marismortui, which is in accordance with differences in their molecular and catalytic properties.…”
Section: Discussionmentioning
confidence: 83%
“…Determination of whether the putative bacterial or archaeal sequences of clusters IA and IB represent functional oxidoreductases or (xylose) dehydrogenases must await their biochemical characterization following expression of the genes that encode them. Eukaryotic xylose dehydrogenases-dimeric DDs, (cluster II), which probably represent a novel family of dehydrogenases (1,2), and archaeal glucose dehydrogenases (cluster III), which belong to the medium-chain dehydrogenase-reductase superfamily (26), form distinct phylogenetic clusters separate from the xylose dehydrogenase from H. marismortui, which is in accordance with differences in their molecular and catalytic properties.…”
Section: Discussionmentioning
confidence: 83%
“…The recombinant proteins were overexpressed in Escherichia coli BL21 (DE3), and the resulting proteins were purified as described in detail elsewhere (6,10). Since the Y180F mutant had extremely low activity under standard assay conditions, the eluants from the chromatography columns were monitored by SDS-PAGE (16) on 12.5% gels.…”
Section: Methodsmentioning
confidence: 99%
“…A recent report on the substrate specificity has shown that dimeric DD efficiently oxidizes several pentoses and is identical with NADP ϩ -dependent D-xylose dehydrogenase (EC 1.1.1.179) (9). The cloning of cDNAs for dimeric DDs of human and the above four animals (10) revealed that the enzymes of these species with 82-94% sequence identities show no homology with the monomeric DDs and cis-dihydrodiol dehydrogenases, which belong to the aldo-keto reductase family (11) and short-chain dehydrogenase/reductase family (12), respectively. However, dimeric DD shows sequence similarity to putative gene products of microorganisms and Zymomonas mobilis glucose-fructose oxidoreductase (GFO, EC 1.1.99.28), and we proposed that these proteins constitute a new protein family (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amino Acid Sequence Analysis of L-Arabinose 1-DehydrogenaseProtein-BLAST analysis revealed that L-arabinose 1-dehydrogenase is a putative member of the Gfo/Idh/MocA protein family, which includes GFOR (18 -20), D-xylose 1-dehydrogenase (21), dimeric dihydrodiol dehydrogenase (DD) (38), and myo-inositol 2-dehydrogenase (39) (Fig. 7A).…”
Section: Cloning Of the Gene Encoding L-arabinose 1-dehydrogenase Andmentioning
confidence: 99%